Determination of the G and P types of previously nontypeable rotavirus strains from the African Rotavirus Network, 1996-2004: Identification of unusual G types - Esona, M.D.; Steele, A.D.; Kerin, T.; Armah, G.E.; Peenze, I.; Geyer, A.; Page, N.; Nyangao, J.; Agbaya, V.A.; Trabelsi, A.; Tsion, B.; Aminu, M.; et al. (Journal of Infectious Disease, 2010)
A total of 215 nontypeable rotavirus samples collected from children <5 years of age by members of the African Rotavirus Network were characterized using reverse-transcription polymerase chain reaction analysis and sequencing. The most predominant strain identified was P[8]G1 (46.9%). Genotypes P[8]G10, P[8]G8, P[6]G8, and P[7]G5 were also detected at frequencies varying from 0.5% to 2.3%. This study suggests that reassortment of unusual G types into a background of globally common genotype P[8] strains may be a major mechanism of generating rotavirus diversity. Nucleotide substitutions at the P[8], P[6], and G1 primer binding sites accounted for the failure to type these strains initially. Hence, these findings highlight the need for regular evaluation of rotavirus genotyping methods.